C–H Functionalization Strategies in the Naphthalene Series: Site Selections and Functional Diversity - Large, Benjamin; Prim, Damien (Synthesis, 2020)
Naphthalene is certainly not a common arene. In contrast to benzene, the bicyclic feature of naphthalene offers multiple differentiable positions and thus a broad diversity of substitution patterns. Naphthalene is a central building block for the construction of elaborated polycyclic architectures with applications in broad domains such as life and materials sciences. As a result, C–H functionalization strategies specially designed for naphthalene substrates have become essential to install valuable substituents on one or both rings towards polysubstituted naphthalenes. This short review provides a focus on uncommon substitution patterns; however, classical ortho C–H activation is not covered.1 Introduction2 C–H Functionalization Using a Directing Group Located at Position 12.1 Functionalization on the Ring Bearing the DG: 1,3-Substitution Pattern2.2 Functionalization on the Ring Bearing the DG: 1,4-Substitution Pattern2.3 Functionalization on the Neighboring Ring: 1,6-, 1,7- and 1,8-Substitution Patterns3 C–H Functionalization Using a Directing Group Located at Position 23.1 Functionalization on the Ring Bearing the DG: 2,4- and 2,1-Substitution Patterns3.2 Miscellaneous Substitution Patterns4 Bis C–H Functionalization4.1 Symmetrical Bisfunctionalization: 1,2,8-Substitution Pattern4.2 Symmetrical Bisfunctionalization: 2,3,1-Substitution Pattern4.2 Unsymmetrical Bisfunctionalization: 2,3,1-Substitution Pattern4.3 Symmetrical Bisfunctionalization: 2,4,8-Substitution Pattern5 Conclusion and Outlook
Keywords: naphthalene; C–H functionalization; directing groups; selectivity; catalysis